New targeted therapies for malignant lymphoma based on molecular heterogeneity. Issue 1 (2nd January 2017) - Horn, Heike; Staiger, Annette M.; Ott, German
ABSTRACT: Introduction : Owing to tremendous advances in the understanding of mechanisms involved in the pathogenesis of malignant tumors an emerging field of novel targeted drugs has evolved within the last decade. This is of particular interest also for malignant lymphomas, constituting a heterogeneous tumor category with substantial variation in clinical outcome, ranging from indolent forms that do not require treatment over years to aggressive cases for which an immediate treatment is mandatory. The elucidation of different molecular strategies adopted by malignant cells has led to a profound profiling of tumor-specific features and consequently resulted in the development of new targeted therapies. Areas covered : A review of currently tested tailored approaches, in particular in B-cell lymphomas (B-NHL), ranging from monoclonal antibodies to inhibition of intrinsic and extrinsic effector molecules. These approaches are currently tested in several subtypes of B-NHL both in preclinical studies and in clinical trials and are summarized within this review. Expert commentary : Considering how quickly basic scientific discoveries could meanwhile be transferred to clinical trials and approvals, future perspectives for novel tailored therapeutic strategies are promising.